Nova acta Academiae scientiarum imperialis petropolitanae. Praecedit historia... - Imperatorskai͡a akademīi͡a nauk (Russia) (Petropolis : Typis Academiae Scientiarum, 1787)
Each volume includes "Histoire" and "Extraits des mémoires" in French. The unabridged memoirs are chiefly in Latin.
Engraved title vignette.
Mode of access: Internet.
Superseded by Mémoires de l'Académie impériale des sciences. 5th series.
Preceded by its Acta, 1777-1782.
Keywords: Science -- Societies, etc. -- Periodicals; Science -- Periodicals